Design and development of a low-cost, eco-friendly forklift for sustainable logistics management - Asif Jalal; Muhammad Farooq; Izza Anwer; Nasir Hayat; Adeel Munir; Imran Zahid; Noreen Sher Akbar; M. Hamza; M. Nouman; Fahid Riaz (Frontiers in Built Environment, 2025)
The U.S. Occupational Safety and Health Administration’s (OSHA) most recent estimates show that between 35,000 and 62,000 injuries occur every year due to forklift-related accidents. According to the National Safety Council (NSC) data, approximately 78 fatalities are reported every year. Moreover, manual loading and unloading of heavy items is time-consuming and poses significant risks to workers in small and crowded warehouses. To address these safety and efficiency concerns cost-effectively, an automated robotic forklift prototype was developed. The key features of this industrial robot include full rotational mobility with a zero-degree turning radius, which reduces the time and space required to turn around corners. It can be operated remotely via a mobile phone using Bluetooth or wi-fi. The motion control system, based on the ESP-32 microcontroller, significantly enhances its operational efficiency compared to manual operation. This study evaluates the performance of the robotic forklift prototype, cost-effectiveness, with loading and unloading capabilities as effective solutions to the challenges faced by workers. Additionally, structural analysis using Ansys confirmed that the design can safely withstand forces 60% greater than the intended design load of 50 N. Furthermore, the maximum stress experienced by the fork is 67% below the material yield strength, further demonstrating robustness and reliability. The integration of advanced technology and Eco-friendly design positions this forklift as a viable and sustainable option for improving material handling in various industrial sectors.